Can Differences in International Prices Measure Unequal Exchange in International Trade?. (1st October 2013) - Subasat, Turan
Abstract : This article discusses the limitations of using the deviations in international prices as a measure of unequal exchange. It argues that international prices are formed in a complex manner and lower international prices for low income countries cannot simply be considered as evidence for unequal exchange. The empirical validity of the measure is also questionable.